Mental Health Literacy and Stigmatizing Attitudes Towards Mental Illness Among Faculty of Health Sciences Students - Tuğçe Doğrul; Meltem Meriç (Artuklu Health)

(untitled)
Introduction: Mental health literacy plays a crucial role in enabling individuals to understand mental illnesses and reduce stigmatizing attitudes. This study aimed to assess the mental health literacy levels of health sciences faculty students, evaluate their stigmatizing attitudes toward mental disorders, and determine the relationship between these variables.Method: The study population consisted of 954 students enrolled in the faculty of health sciences at a university during the 2022-2023 academic year. Using a 95% confidence level and a 5% margin of error, the sample size was calculated as 274 students, and data collection was completed with 294 participants to account for potential data loss. Data were collected using a personal information form, the Mental Health Literacy Scale, and the Mental Illness Stigma Scale for health professionals. Descriptive statistics, t-tests, and ANOVA were applied for data analysis.Results: The mean age of the participants was 22 years; 83.7% were female, 94.9% were single, and 29.9% were fourth-year students. The mean mental health literacy score was 101.163±16.570, while the mean stigmatization score was 58.344±11.884. A significant negative and strong correlation was found between mental health literacy and stigmatization (r=-0.75; p<0.05).Conclusion: Higher levels of mental health literacy are associated with lower levels of stigmatization toward mental illnesses